PERAN TEKNOLOGI INFORMASI DALAM AKTIFITAS DAKWAH: Menelusuri Signifikansi Dakwah Online - Rusli, Rusli (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi; Vol 9 No 1 (2013), 2013)
This paper  deals with the role of information technology in da 'wa   acivities. It concludes  that  because  of the spread  of Internet, online da'wa as a kind of new model of Islamic preaching emerges. This kind of da'wa focused on the socialization that includes process of al-ta 'aruf (acquaintance) and   al-ta'aluf (harmony) with the target of object of Islamic preaching ( al-mad' u ). This is carried out based on the three levels of online interaction, which includes spreading, participation and mobilization.